Is Destira my destiny? : whether, when, and how to join one's small family business - Ward, John L.; Zsolnay, Carol (London : Kellogg School of Management, 2018)
In mid-2012, after successful years in large public companies and obtaining an MBA, middle daughter Jen, 32, is trying to decide whether the time is right for her to enter her mother and sister's small family business to grow it further. Destira, Inc. was a designer/manufacturer of gymnastics wear for girls, headquartered in California. Donna Levy founded the company in 1990, after years of making leotards for her three daughters, who were competitive youth gymnasts, and getting requests from other parents to make the garments for their own children. In 2005, when Donna's oldest daughter, Jodi, joined Destira, Donna gave her a 50 percent equity stake. Between then and year-end 2011, the pair grew the revenues from $550,000 to $1.06 million, increased the number of outlets carrying the brand, upgraded the internal accounting/operations software, and added an online direct-to-customer retail business. The case shows realistic considerations for the individual, family, and business when evaluating whether or not to commit to join the family enterprise.
Originally Published InWard, J. L., & Zsolnay, C. (2018). Is Destira my destiny? Whether, when, and how to join one's small family business. 5-113-006. Evanston, IL: Kellogg School of Management at Northwestern University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Destira, Inc; Clothing trade -- United States -- Case studies; Textile industry -- United States -- Case studies